Glycan processing in gut microbiomes. (June 2022) - La Rosa, Sabina Leanti; Ostrowski, Matthew P; Vera-Ponce de León, Arturo; McKee, Lauren S; Larsbrink, Johan; Eijsink, Vincent G; Lowe, Elisabeth C; Martens, Eric C; Pope, Phillip B
Graphical abstract: Highlights: Gut microbiomes and their enzymes enable processing of glycans consumed or secreted by the host. Common mechanisms of glycan utilization are found across gut microbiomes from diverse hosts. Functional omics assist in discovering new glycan degradation strategies and cross-feeding interactions. Targeted dietary interventions can be designed to target specific microbial machinery for glycan processing. Abstract : Microbiomes and their enzymes process many of the nutrients accessible in the gastrointestinal tract of bilaterians and play an essential role in host health and nutrition. In this review, we describe recent insights into nutrient processing in microbiomes across three exemplary yet contrasting gastrointestinal ecosystems (humans, ruminants and insects), with focus on bacterial mechanisms for the utilization of common and atypical dietary glycans as well as host-derived mucus glycans. In parallel, we discuss findings from multi-omic studies that have provided new perspectives on understanding glycan-dependent interactions and the complex food-webs of microbial populations in their natural habitat. Using key examples, we emphasize how increasing understanding of glycan processing by gut microbiomes can provide critical insights to assist 'microbiome reprogramming', a growing field that seeks to leverage diet to improve animal growth and host health.